APPLICATION OF INDONESIAN NURSING DIAGNOSIS STANDARDS IN NURSING DIAGNOSIS DOCUMENTATION IN CHILDREN WITH DENGUE HEMORRHAGIC FEVER - Tyas, Anestasia Pangestu Mei; Nuriantari, Risma Dysta; Mardhika, Amellia; Ilkafah, Ilkafah; Fadliyah, Lailatul; Sulpat, Emuliana (Universitas Airlangga, 2024)
Introduction: The Indonesian National Nurses Association has developed nursing language standards adapted to cultural differences and uniqueness of Indonesian nursing services, namely the Indonesian Nursing Diagnostic Standards. Dengue Hemorrhagic Fever cases in Indonesia have experienced a shortening cycle, which has led to a rise in the incidence rate (IR) and a fall in the case facility rate (CFR). This study was to learn how to describe the application of the Indonesian Nursing Diagnosis Standards (SDKI) in documenting nursing diagnoses in children with Dengue Hemorrhagic Fever (DHF). Methods: Retrospective descriptive research design with secondary data. The secondary data used in the study, namely sourced from medical records from February 1, 2021 - March 31, 2022. The number of samples is 30 medical records using the total sampling technique. Data collection using observation sheet. Data analysis uses univariate analysis. Results: Most of the priority nursing diagnosis labels in DHF pediatric patients are by the Indonesian Nursing Diagnosis Standards, namely hyperthermia. However, all the writing of actual nursing diagnoses does not comply with the Indonesian Nursing Diagnosis Standards, which consists of writing three parts: [problems] related to [cause/related factors] as evidenced by [signs/symptoms], but the writing of nursing diagnoses is only in the form of problems or problems and causes. Conclusions: There needs to be a refreshing knowledge about the Indonesian Nursing Diagnosis Standards to improve the knowledge and skills of nurses in documenting nursing diagnoses.